2009
DOI: 10.1380/ejssnt.2009.157
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Uniaxial Assembly of Polyaromatic Monolayers

Abstract: The control of spatial arrangements of molecular building blocks on surface opens the foundational step of the bottom-up approach toward future nanotechnologies. Contemporarily, the domain size of monolayers exhibiting crystallinity falls in the submicron scale. Developed herein is a method that allows the alignment of polyaromatics with one-single domain for as long as ∼7 mm. Even more exciting is the fact that the method is applicable to every laboratory with negligible cost. The monolayers are prepared simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Physically separating the two sinter‐prone metals would be a fundamental solution to the sintering problem, as opposed to regulating metal‐support interactions or metal synergies to inhibit sintering [70] . Some commercial catalysts utilize zoned or layered catalysts, where the coating and active metal of the zoned catalyst varies along the length of the monomer, and layered catalysts sequentially deposit multiple layers of active metal on the monomer to inhibit alloy formation [71–75] . Xin and his co‐workers investigated the stability of Rh and Pd in three‐way catalysts.…”
Section: Active Center Construction Strategies In Rh‐based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physically separating the two sinter‐prone metals would be a fundamental solution to the sintering problem, as opposed to regulating metal‐support interactions or metal synergies to inhibit sintering [70] . Some commercial catalysts utilize zoned or layered catalysts, where the coating and active metal of the zoned catalyst varies along the length of the monomer, and layered catalysts sequentially deposit multiple layers of active metal on the monomer to inhibit alloy formation [71–75] . Xin and his co‐workers investigated the stability of Rh and Pd in three‐way catalysts.…”
Section: Active Center Construction Strategies In Rh‐based Catalystsmentioning
confidence: 99%
“…The T 50 values of Pt/Ce‐Rh/LA for NO and HC were 380°C and 370°C, respectively. Lee and his co‐workers investigated the kinetics of the (111) surfaces of Pt, Rh, and Pd in three‐way catalyst reactions by DFT calculations [75] . They found that Pt and Pd exhibited similar kinetic behaviors, with H 2 playing an important role in assisting NO dissociation and removing O* from the Pt surface.…”
Section: Active Center Construction Strategies In Rh‐based Catalystsmentioning
confidence: 99%